Analisis Realisme Ofensif Amerika Serikat Keluar dari Intermediate Range Nuclear Force Treaty (INF Treaty) pada 2019 - Yuliana P.S, Marga Rettha; Suwecawangsa, Adi Putra; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT                                                                                    This research aims to analyze the behavior of United State who decide to withdraw from Intermediate-range Nuclear Force Treaty (INF Treaty). INF Treaty is a post cold war agreement between the United States and Uni Soviet which limited the use and development of ground missile with the range of 500-5.500 km. The INF Treaty became the treaties that eliminates missile threat in the Euro-Atlantic region. After more than thirty years, United State decided to withdraw from the agreement even though the dcision might be dangerous for Euro-Atlamtic region. This research uses an explanative qualitative method, and literature sources to collect the data. Therefore, Researcher uses a theory, which is offensive realism in order to answer the motive behind United State’s withdrawal. These research perceives that the treaty was not accordance anymore with the United States objective in developing missile to achieve hegemony in missile development. Keywords : United States, Russia, INF Treaty, Offensive Realism